PROBLEMS OF CHILDHOOD AND EDUCATION IN CHARLES DICKENS’ WORKS - Abdukadirova Gulruh Baxodir qizi; Akmalxonov Saidfozil Akmalxonovich (Лучшие интеллектуальные исследования, 2024)
Abstract: Charles Dickens, one of the most important novelists of the Victorian era, deals extensively with themes of childhood and education in his literary works. This summary examines Dickens' depiction of these themes and analyzes how he used his novels to criticize the social conditions of his time. Dickens often portrayed childhood as a time of vulnerability and exploitation, emphasizing the plight of poor children who were exposed to neglect, abuse, and exploitation. Through characters such as Oliver Twist, David Copperfield, and Pip in Great Expectations, Dickens revealed the harsh realities faced by orphans and destitute children in Victorian society. Additionally, Dickens investigated the educational system of his time, revealing its injustices, inefficiencies, and moral deficiencies. He criticized the education system's rigid class structure for hindering social mobility and perpetuating inequality. Through his vivid storytelling and his sharp social commentary, Dickens advocated reform in child welfare and education and emphasized the importance of compassion, empathy, and human dignity. This abstract provides insight into Dickens' deep commitment to issues of early childhood and education, by examining selected novels such as Oliver Twist, David Copperfield, and Hard Times, and explores his deep commitment to social justice and humanity, highlights his enduring legacy as a champion of human values.